Mesoporous silica–carbon composites fabricated by a universal strategy of hydrothermal carbonization: controllable synthesis and applications. Issue 48 (31st July 2018) - Sun, Xitong; Yu, Wei; Yan, Jingyu; Li, Jiaqi; Jin, Gaowa; Feng, Jiatao; Guo, Zhimou; Liang, Xinmiao
Abstract : A carbon layer with controlled thickness can be coated on the surface of mesoporous silica through the hydrothermal carbonization strategy. Abstract : Mesoporous silica–carbon composite materials, with homogeneous and thickness-controllable carbon coating, were synthesized by using a universal strategy of hydrothermal carbonization, and the carbon layer could be coated on the surface of ordered and disordered mesoporous silica. The electrostatic interaction between amino-modified silica and hydrothermal carbon was regarded as the main driving force for the formation of homogeneous carbon coverage on the silica surface. The obtained composites showed high graphitization degree, and controlled morphology (shape and particle size) and pore size by adjusting the species of carriers and hydrothermal conditions. The application results demonstrated that a thin carbon layer possessed high adsorption capacities for dyes, and the composite could be rapidly recovered by sedimentation (10 min) after adsorption with 30 μm spherical silica gel as the carrier. Besides, baseline chromatographic separation of oligosaccharide isomers could be achieved on the silica–carbon column. These results indicated that the silica–carbon composites should be promising functional materials for the large-molecule-involving processes such as adsorption and chromatographic separation.